Solitary Wave Solutions to the Multidimensional Landau–Lifshitz Equation - Ahmad Neirameh (Advances in Mathematical Physics)
In this paper, we study the different types of new soliton solutions to the Landau–Lifshitz equation with the aid of the auxiliary equation method. Then, we get some special soliton solutions for this equation. Without the Gilbert damping term, we present a travelling wave solution with a finite energy in the initial time. The parameters of the soliton envelope are obtained as a function of the dependent model coefficients.